Prevalence and Diagnostic Evaluation of Endometritis in Infertile Mares: Bacteriological, Cytological, and Haematological Correlations - Chaudhari, Dhruv B; Chaudhari, Dinesh V; Bharai, Munja J; Mahla, Jalendra K (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The study was conducted on infertile mares from stud farms around Anand and those presented to the Veterinary Clinical Complex,  Kamdhenu University, Anand, to assess the prevalence of infertility and endometritis, identify major uterine pathogens, and evaluate  age-related haematological and cytological changes. Thirty mares with a history of infertility were examined. The incidence of  infertility and endometritis increased notably with age, as mares above eight years showed a higher prevalence of uterine infection,  suggesting age-related degeneration of uterine defense mechanisms. Bacteriological examination revealed Escherichia coli as the  predominant isolate, followed by Streptococcus spp., Staphylococcus spp., Proteus spp., Pseudomonas spp., and Klebsiella spp. β-haemolytic  Streptococcus was associated with elevated uterine pH, while E. coli infection showed no pH correlation. Cytological examination  showed increased polymorphonuclear neutrophils (PMNs), confirming endometrial inflammation. Haematological analysis indicated  mild immunosuppression, reflected by slightly reduced leukocyte and lymphocyte counts, while erythrocytic and platelet values  remained largely within normal limits, with a minor decrease in platelet mass. In conclusion, endometritis was identified as a major  cause of infertility in mares, with higher susceptibility in older animals. The predominance of E. coli and Streptococcus spp., coupled  with supportive cytological and haematological changes, highlights the importance of integrated diagnostic approaches for effective  detection and management of uterine infections in mares.
Keywords: Age-related infertility, Bacteriology, Cytology, Equine endometritis, Haematology, Escherichia coli, Infertility